2005
DOI: 10.1111/j.1525-1314.2005.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocean‐floor hydrothermal metamorphism in the Limousin ophiolites (western French Massif Central): evidence of a rare preserved Variscan oceanic marker

Abstract: The Limousin ophiolite is located at the suture zone between two major thrust sheets in the western French Massif Central. This ophiolitic section comprises mantle-harzburgite, mantle-dunite, wehrlites, troctolites and layered gabbros. It has recorded a static metamorphic event transforming the gabbros into undeformed amphibolites and the magmatic ultramafites into serpentinites and/or pargasite-bearing chloritites. With various thermobarometric methods, it is possible to show that the different varieties of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 74 publications
(192 reference statements)
0
23
0
Order By: Relevance
“…http://doc.rero.ch the Massif Central domain, (Limousin area, Pin and Marini, 1993;Briand et al,1995;Berger et al, 2005). The Upper Cambrian oceanisation of some marginal basins in a context of back-arc rifting, scattered through the Iberian Allochthonous (Arenas et al, 2007a,b) and the formerly nearby areas of rifting like the Ossa Morena Zone (Sánchez García et al, 2003;Quesada, 2006) could equally represent the westward continuation of the Chamrousse Zone, if a more cylindrical model is applied for the Gondwana margin.…”
Section: Cambrianmentioning
confidence: 99%
“…http://doc.rero.ch the Massif Central domain, (Limousin area, Pin and Marini, 1993;Briand et al,1995;Berger et al, 2005). The Upper Cambrian oceanisation of some marginal basins in a context of back-arc rifting, scattered through the Iberian Allochthonous (Arenas et al, 2007a,b) and the formerly nearby areas of rifting like the Ossa Morena Zone (Sánchez García et al, 2003;Quesada, 2006) could equally represent the westward continuation of the Chamrousse Zone, if a more cylindrical model is applied for the Gondwana margin.…”
Section: Cambrianmentioning
confidence: 99%
“…2005). One conclusion of these investigations is that an ocean‐floor hydrothermal metamorphism is ubiquitous in the vicinity of a paleo‐ridge (Berger et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Mével et al 1978;Girardeau & Mével, 1982;Berger et al 2005). One conclusion of these investigations is that an ocean-floor hydrothermal metamorphism is ubiquitous in the vicinity of a paleo-ridge (Berger et al 2005). In the Godzilla Megamullion, Harigane et al (2008) showed that hydrothermal alteration resulted in retrograde metamorphism associated with deformation on the Fe-Ti oxide gabbroic body in the West Leg Ridge (Fig.…”
Section: Ocean-floor Hydrothermal Metamorphism In Godzilla Megamullionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, although controversial (Berger et al, 2005), the nappe stacking model is still the prevailing one (Faure et al, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 97%